Association between hemoglobin/red blood cell distribution width ratio and acute kidney injury in sepsis and heart failure patients - Petherson Mendonça dos Santos; Isabele Pardo; Maria Carolina Borges Pereira de Almeida; Rafael Santana de Oliveira; Fernanda Gabas Miglioli; Beatriz Mota Busnardo; Felipe Prieto Siqueira; Daniela Harsanyi; Andreia Pardini; Bruno Bravim; Anna Carolina de Rizzo Cantoni Rosa; Kirliane de Sousa Rodrigues Lacerda; et al. (PLoS ONE, 2026)
Introduction The hemoglobin/red blood cell distribution width (Hb/RDW) ratio has emerged as a potential biomarker for acute kidney injury (AKI), particularly in patients with cardiovascular conditions. This study investigated the relationship between Hb/RDW ratio and AKI incidence in critically ill patients diagnosed with sepsis and heart failure (HF). Methods A retrospective study was conducted with 119 critically ill patients with sepsis and 83 patients with HF, analyzed according to the presence or absence of kidney injury. Multivariable logistic regression identified independent predictors of AKI. Outcomes between higher and lower Hb/RDW groups were compared. Results Patients who developed AKI showed higher C-reactive protein levels, elevated RDW (15.7 ± 2.2 vs. 14.9 ± 1.8; p = 0.01), and higher SAPS 3 scores, along with markedly lower Hb concentrations and Hb/RDW ratios (75.1 ± 1.6 vs. 85.5 ± 1.9; p < 0.001). In multivariable analysis, serum urea (OR 1.016; 95% CI 1.005–1.027 per mg/dL), SAPS 3, and Hb/RDW ratio (OR 0.977; 95% CI 0.959–0.996) were independently associated with AKI. Patients with a lower Hb/RDW ratio had higher frequencies of AKI, kidney-replacement therapy, red-cell transfusion, and mortality. During a 7-year follow-up, progression to dialysis-dependent stage V chronic kidney disease (CKD-V) occurred in 10.8% of HF patients and 2.5% of sepsis patients, indicating that a lower Hb/RDW ratio was also associated with worse long-term renal outcomes. Conclusion The Hb/RDW ratio is independently associated with AKI and may also reflect long-term kidney prognosis, representing a cost-effective and readily available ICU marker to identify patients at risk for both acute and chronic renal deterioration in sepsis or HF.